Determination of the suitabilty of the primary and secondary sludge by sappi enstra as landfill capping material - Brown, Riva Anne (My University, 2016)
As attempts are made, through new regulations, toimprove landfill standards in South Africa, while competition is experienced for limited resources, acceptable alternative technologies for landfills are sought. Paper mill pulps and sludges have been tested. and used, extensively for capping landfills, particularly in the USA. The purpose of this study was to determine whether the pulp and combined sludge produced by the Sappi Enstra Mill. in Springs South Africa. is suitable for the capping of their landfill. Trends in the landfilling of waste. the use of various hydraulic barrier systems. and comparative testing programmes are reviewed. Laboratory and field tests indicate that the Enstra pulp and combined sludge <Iresuitable for the capping of the landfill as they meet hydraulic conductivity specifications. and results are similar to the tests conducted in the USA. In addition. the use of the pulp and sludge has advantages over the use of clay.
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 1997